Introduction to Plastics Engineering - Shrivastava, Anshuman, author 648528; ScienceDirect (Online service) 7722 (Cambridge : William Andrew, 2018)
Introduction to Plastics Engineering provides a single reference covering the basics of polymer and plastics materials, and their properties, design, processing and applications in a practical way. The book discusses materials engineering through properties formulation, combining part design and processing to produce final products. This book will be a beneficial guide to materials engineers developing new formulations, processing engineers producing those formulations, and design and product engineers seeking to understand the materials and methods for developing new applications. The book incorporates material properties, engineering, processing, design, applications and sustainable and bio based solutions. Ideal for those just entering the industry, or transitioning between sectors, this is a quick, relevant and informative reference guide to plastics engineering and processing for engineers and plastics practitioners.